Zarządzanie łańcuchem podaży w organizacjach sieciowych (kształtowanie zależności międzyorganizacyjnych) - Mokwa, Zdzisław; Nogalski, Bogdan (Managing Supply Chains in Network Organizations (Shaping of the Organizational Relations), 2005)
In the paper, authors analyse theoretical aspects of the formation of different variants of supply chain' management. They see organizations working as a network, as the collective subject of organization and configuration of the chain. Main object of consideration is therefore the shaping of the inter-organizational, or network, relations.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1078, s. 115-122